Ensemble Modeling of Radiation Belt Electron Flux Decay Following a Geomagnetic Storm: Dependence on Key Input Parameters - Man Hua; Jacob Bortnik; Adam C. Kellerman; Enrico Camporeale; Qianli Ma (Space Weather)
Abstract We perform an ensemble of quasi‐linear diffusion simulations of the radiation belt electron flux decay for ∼6 days at L = 3.5 during the recovery phase of the storm on 7 November 2015, where plasmaspheric hiss dominantly drives the electron flux decay process. Based on Van Allen Probes measurements, we use percentiles to sample distributions of the four key input parameters, which are the hiss wave amplitude Bw, hiss wave peak frequency fm, background magnetic field B0, and electron density Ne, with 11 points representing that range of each input, leading to 114 (∼14,600) ensemble members. By developing a Lookup Table method to rapidly calculate the time‐dependent diffusion coefficients, the changing wave environment at every time step is incorporated into our ensemble simulations. The comparison between the ensemble simulations and observations reveals the influence of uncertainties in the input parameters on the simulated electron fluxes. Our results demonstrate that the perturbations in Bw are the primary contributors for discrepancies between modeled and observed electron fluxes, while the simulation errors caused by variations in fm and Ne are strongly energy‐dependent. The simulated electron flux using the wave parameters observed at the 50th percentile agrees with observations, and most of the simulation errors increase with decreasing observational probability density of the parameters, with the largest log accuracy ratio of ∼14. Our physics‐based ensemble modeling provides the essential information about the robustness of radiation belt simulation and forecast considering the uncertainties in the plasma wave measurement or parameterization.